PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA PETUGAS PADA DIREKTORAT POLISI PERAIRAN (DITPOLAIR) PEKANBARU - Muhammad Al Ghazali; Marnis '; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of intellectual, emotional intelligence and spiritual intelligence simultaneously on the performance of the Direktorat Polisi Perairan (Ditpolair) Pekanbaru. To determine the influence of intellectual, emotional intelligence and spiritual intelligence partially on the performance of the Direktorat Polisi Perairan (Ditpolair) Pekanbaru. And to determine which variables are the dominant influence on the performance of the Direktorat Polisi Perairan (Ditpolair) Pekanbaru. In this study, the population is Water Police Directorate officers (Ditpolair) Pekanbaru, amounting to 82. To undertake research sample taken using census method that sets the entire population as the study sample. Analysis of the data in this study will use a multiple regression model. The results of this study stated that intelligence (X1), emotional intelligence (X2) and spiritual intelligence variable (X3) simultaneously have significant affects the performance. Then partially these three variables also have a significant effect. Variable spiritual intelligence ( X3 ) is a dominant variable affecting the performance Ditpolair Riau Police officers because it has a regression coefficient greater than the other independent variables (intellectual and emotional intelligence). Effect of intellectual, emotional intelligence and spiritual intelligence on the performance simultaneous based Adjusted R2 value is equal to 0.476 or 47.60 % , while 52.40 % influenced by other variables not examined in this study as a factor compensation motivation, environment work, supervision and so forth.Keywords : Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence, Performance